Strategi Pemasaran Industri Rumah Tangga Arang Tempurung Kelapa (Studi Kasus Pada Industri Rumah Tangga Bapak Abdul Razak Di Cimanggis, Ciputat, Tangerang Selatan) - Zelivieska Bintang Maharani; Ratna Pratiwi; Qory Anissa; Dwi Ratnasari; Sugeng Waluyo; Pitri Yandri (ITB Ahmad Dahlan Jakarta, 2018)
In South Tangerang city, there are many home industries producing charcoal shell. One of the industry is practiced by Mr. Abdul Razak in Ciputat District. According to some studies, in general the home industry is facing many problems, one of which is a weak in marketing strategy. Based the information, this article reports the marketing strategies implemented by the industry. With SWOT approach, we informed that the position of industrial strength lies in good relationships with suppliers. And the weakness is that the marketing activities carried out only through word of mouth. We recommend that the industry need to consider the using of banners or internet-based technology utilization for the marketing strategies.